Prevalence of communicable, non-communicable diseases, disabilities and related risk factors in Khyber Pakhtunkhwa Pakistan: Findings from the Khyber Pakhtunkhwa Integrated Population and Health Survey (2016-17). - Ziaul Haq; Saima Afaq; Muhammad Ibrahim; Zala; Muhammad Asim (PLoS ONE)
Introduction Pakistan is facing a triple burden of diseases: communicable diseases (CDs), non-communicable diseases (NCDs) and disabilities. There is limited evidence on the patterns of these diseases in Pakistan, specifically Khyber Pakhtunkhwa. Additionally there remains limited study on the impact of sex-, age and setting-stratified morbidities in Khyber Pakhtunkhwa. Objectives The objective of this study was to present the demographic characteristics and the burden of locally-specific CDs (hepatitis B and C, TB, AIDS), NCDs (diabetes, renal diseases, asthma, epilepsy, coronary heart diseases, cancer, hypertension, cholesterol, thalassemia), and disabilities (congenital, post-disease, post-injury, paralysis) stratified by sex, age and setting in the Khyber Pakhtunkhwa province of Pakistan. Material and methods The Khyber Pakhtunkhwa Integrated Population and Health Survey (KP-IPHS) was conducted in 2016-17 to gather comprehensive information about the demographic characteristics and locale-specific health-related issues of the people of Khyber Pakhtunkhwa, Pakistan. This cross-sectional survey was conducted in 24 districts across all 7 divisions of Khyber Pakhtunkhwa on population ageing ≥18 years. A total of 20704 respondents were taken from primary (n = 1061) and secondary sampling units (n = 15724), designed with considerations for urban/rural and socio-economic status. Each primary unit included 250-300 households. The sample selection utilised a multi-staged stratified systematic cluster sampling technique, involving the inclusion of every 16th household in rural areas and every 12th household in urban areas. Observations were recorded on demographics, quality of life, physical activity, BMI, disabilities, CDs and NCDs. Results Among all NCDs, hypertension has the highest prevalence (29.2%), showing a significant difference between females (32.7%) and males (25.0%). The proportion of males and females with diabetes is 7.4% and 5.2%, respectively, with a more substantial percentage (11.2%) observed in the ≥50 years' age group compared to 2.5% in the 18-29 years' age group and 5.0% in the 30-49 years' age group. Among the included CDs, hepatitis B and C (0.5% and 0.8%, respectively) are most prevalent. Hepatitis B is more common in females (0.8%) and in rural settings (0.6%) compared to males (0.3%) and urban settings (0.2%), respectively. The prevalence of congenital disabilities is the highest of all disabilities, with a significantly high prevalence in females (5.3%) and rural settings (3.5%) compared to males (0.9%) and urban settings (0.6%) respectively. Furthermore, post-injury, post-disease disabilities, and paralysis significantly increase with age (P < 0.001). Conclusions Our findings show that the prevalence of CDs, NCDs and disabilities varies across sex, age and settings, with a notable prevalence in females and the old-age population (≥50 years). The results emphasise the necessity of public health efforts, such as screening, prevention, and treatment, to tackle the triple burden of CDs, NCDs, and disabilities in Khyber Pakhtunkhwa Pakistan.